Development and Evaluation of an Automated, Home-Based, Electronic Questionnaire for Detecting COPD Exacerbations. Issue 4 (18th December 2015) - Velazquez-Peña, Francisco de B.; Sanchez-Morillo, Daniel; Crespo-Miguel, Mario; Astorga-Moreno, Sonia; Santi-Cano, MJ; Fernandez-Granero, MA; Leon-Jimenez, Antonio
Abstract : Collaboration between patients and their medical and technical experts enabled the development of an automated questionnaire for the early detection of COPD exacerbations (AQCE). The questionnaire consisted of fourteen questions and was implemented on a computer system for use by patients at home in an un-supervised environment. Psychometric evaluation was conducted after a 6-month field trial. Fifty-two patients were involved in the development of the questionnaire. Reproducibility was studied using 19 patients (ICC = 0.94). Sixteen out of the 19 subjects started the 6 month-field trial with the computer application. Cronbach's alpha of 0.81 was achieved. In the concurrent validity analysis, a correlation of 0.80 (p = 0.002) with the CCQ was reported. The results suggest that AQCE is a valid and reliable questionnaire, showing that an automated home-based electronic questionnaire may enable early detection of exacerbations of COPD.